Selective forex trading : - Snellgrove, Don (John Wiley, 2008)
Selective Forex Trading skillfully outlines author Don Snellgrove’s S90/Crossover: an independently verified technical indicator that has provided traders with the ability to achieve over 100 consecutive Forex trades without a single loss. Whether you’re a seasoned professional or just getting started, this approach—which is based on historical resistance and support points within a trading range—can assist you in entering and exiting positions for the greatest profits possible.